A new two-stage separation procedure for the IDMS based quantification of low Pd and Pt amounts in automotive exhaust emissions. Issue 2 (12th December 2014) - Vogl, Jochen; Meyer, Christian; Koenig, Maren; Becker, Dorit; Noordmann, Janine; Rienitz, Olaf; Mamakos, Athanasios; Riccobono, Francesco
Abstract : A two-step separation procedure for the IDMS-analysis of Pd and Pt was developed enabling effective separation from interfering elements. Abstract : A two-step separation procedure for the quantification of Pd and Pt in automotive exhaust emissions using isotope dilution mass spectrometry was established using a combination of cation and anion exchange chemistry. AG 50W-X12 was used as cation exchange resin and DGA as weakly basic anion exchange resin. This procedure enabled the effective separation of Pd and Pt from the matrix and from interfering elements. Additionally Pd and Pt were collected in separate chromatographic fractions, which increased the precision of the isotope ratio determination by separate measurements using single collector sector field ICPMS. The analytical procedure was validated by analysing the synthetically prepared samples and the certified reference materials BCR-723 (road dust) and IAEA-450 (algae). For the SI-traceable results complete uncertainty budgets were calculated yielding relatively expanded uncertainties ( k = 2) of ≈1% for analyte masses in the ng range. Procedure blanks of 55 pg Pd and 3 pg Pt were obtained. The detection limits were calculated as 12 pg for Pd and 7 pg for Pt. Additionally, Pd and Pt blank levels of different filter materials are presented as well as the first results for automotive exhaust particles collected on cellulose filters.